Construction of the green infrastructure network for adaption to the sustainable future urban sprawl: A case study of Lanzhou City, Gansu Province, China - Xin Zhang; Yunying Ren; Dan Zhang; Kongming Li (Ecological Indicators, 2022)
Nature-based green infrastructure (GI) is considered as a sound solution to mitigate the urban issues resulting from rapid urbanization. It is exceedingly essential to construct GI network for adaption to the dynamics of natural and social conditions. However, it has not been well studied until now. In this study, taking Lanzhou City, Gansu Province, China as a case, we proposed an improved framework of GI construction for adaption to sustainable urban sprawl. First, we predicted the land use and land cover (LULC) in Lanzhou City in 2030 by using the FLUS (future land use simulation) model. Then, based on the predicted LULC, we extracted ecological sources and corridors by integrating MSPA (Morphological spatial pattern analysis) and MCR (minimum cumulative resistance) model. Finally, as a case, an optimized GI network for adaption to the future sustainable urban sprawl in Lanzhou City in 2030 was established, which included 10 ecological sources, 56 ecological corridors as well as 19 nodes. In this case study, the improved framework was proven to be reliable, and thus can be promoted to construct the GI network in other regions for adaption to different future scenarios. This case study would provide some new insights for future urban planning both in Lanzhou City and cities in other regions, and then contribute to GI protection and regional ecological security.